Prevalence of Drug Resistance and Associated Mutations in a Population of HIV-1+ Puerto Ricans: 2006–2010 - Lycely del C. Sepúlveda-Torres; Alexandra De La Rosa; Luz Cumba; Nawal Boukli; Eddy Ríos-Olivares; Luis A. Cubano (AIDS Research and Treatment)
This is a continuation of our efforts to maintain a record of the evolution of HIV-1 infection in Puerto Rico by monitoring the expression levels of antiretroviral drug-resistance-associated mutations. Samples from 2,500 patients from 2006–2010 were analyzed using the TruGene HIV-1 genotyping kit and the OpenGene DNA sequencing system. Results show that 58.8% of males and 65.3% of females had HIV-1 with resistance to at least one medication. The average number of HIV mutations was 6.0 in males and 6.1 in females. Statistically significant differences between men and women were recorded in the levels of HIV-1 expressed mutations and antiretroviral drug resistance. The most prevalent antiretroviral medication resistance shifted from zalcitabine to nevirapine and efavirenz in the five-year period. M184V and L63P were the dominant mutations for the reverse transcriptase and the protease genes, respectively, but an increase in the incidence of minority mutations was observed.